Knowledge and Prevalence of Supplements Used by Brazilian Resistance Training Practitioners Before Coronavirus Outbreak - Vancini RL; Rufo-Tavares W; de Paula Oliveira HR; Viana RB; Andrade MDS; Knechtle B; Nikolaidis PT; Gentil P; de Lira CAB (Dove Medical Press, 2021)
Rodrigo Luiz Vancini,1 Weverton Rufo-Tavares,1 Hudson Renato de Paula Oliveira,1 Ricardo Borges Viana,2,3 Marilia dos Santos Andrade,4 Beat Knechtle,5 Pantelis Theodoros Nikolaidis,6 Paulo Gentil,7 Claudio Andre Barbosa de Lira7 1Centro de Educação Física e Desportos, Universidade Federal do Espírito Santo, Espírito Santo, Brasil; 2Escola Superior de Educação Física e Fisioterapia do Estado de Goiás, Universidade Estadual de Goiás, Goiânia, Brasil; 3Faculdade Estácio de Sá, Goiânia, Departamento de Educação Física, Goiânia, Brasil; 4Departamento de Fisiologia, Universidade Federal de São Paulo, São Paulo, Brasil; 5Medbase St. Gallen Am Vadianplatz, St. Gallen and Institute of Primary Care, University of Zurich, Zurich, Switzerland; 6School of Health and Caring Sciences, University of West Attica, Athens, Greece; 7Setor de Fisiologia Humana e do Exercício, Faculdade de Educação Física e Dança, Universidade Federal de Goiás, Goiânia, BrasilCorrespondence: Beat KnechtleFacharzt FMH für Allgemeinmedizin, Medbase St. Gallen Am Vadianplatz, Vadianstrasse 26, St. Gallen, 9001, SwitzerlandEmail beat.knechtle@hispeed.chIntroduction: The use of dietary supplements and ergogenic aids (DSEA) is popular among physical activity enthusiasts. Particularly, resistance training (RT) practitioners represent important DSEA consumers due to its easy access and the appeal of claims related to muscle hypertrophy, aesthetics, and physical performance improvements.Methods: Our aim was to study knowledge, prevalence, and profile of DSEA used by Brazilian recreational RT practitioners. For this, RT practitioners of both sexes (n=129, female=58 and male=71) answered a paper-based questionnaire. The questionnaire was specifically created for the studied population to assess different aspects of the DSEA used and sociodemographic variables.Results: Seventy-seven percent of the participants (n=99) declared that they had already used DSEA. The majority (53%) searched the internet to obtain information about DSEA. Whey protein (66%) was the most used followed by branched chain amino acids (48%).Conclusion: The use of DSEA, before coronavirus outbreak, was popular among RT practitioners; protein and amino acids were the most used DSEA. Most users used internet to obtain information about DSEA. The results suggest the need for appropriate attitude and guidance by health professionals who deal with this population, especially dietitians, nutritionists, and physical training professionals in order to promote best and security practices.Keywords: nutrition, supplements, gyms, resistance training, ergogenic